Whose Call to Answer: Institutional Complexity and Firms’ CSR Reporting - Luo, Xiaowei Rose; Wang, Danqing; Zhang, Jianjun (Academy of Management Journal, 2017)
While research on the disclosure of CSR (corporate social responsibility) recognizes the influence of government regulations and guidelines, less attention has been given to the co-existence of conflicting pressures from the state. We develop a framework wherein CSR reporting is viewed as an organizational response to institutional complexity that arises from the conflicting demands from the central government and local governments, and apply it to publicly listed firms in China after the central government agencies issued guidelines on CSR reporting. Some provincial governments’ high priority given to short-term GDP growth created tension with the central government’s expectations on CSR reporting. Firms with attributes that increase scrutiny from both institutional constituencies experienced heightened tension, and they responded with early adoption but low-quality reports. Our framework was supported through a longitudinal analysis between 2008 and 2011. Our study contributes to the literature on CSR disclosure by uncovering the impact of conflicting government pressures, and advances research on institutional complexity by identifying a specific decoupling response.